Quality aspects in the development of pelletized dosage forms - Surendra Agrawal; Joneth Fernandes; Fuzail Shaikh; Vishwa Patel (Heliyon, 2022)
The aim of this work was to identify and collate the major common challenges that arise during pellet development. These challenges focus on aspects right from raw material properties until the final drying process of the pelletization. The challenges associated with the particle size of drug and excipients, physicochemical properties, drug excipient interaction and the effect of type/grade and amount of raw material on the pellet properties are covered in this review. Technological and process related challenges within the commonly used pelletization techniques such as extrusion-spheronization, hot-melt extrusion and layering techniques are also emphasized. The paper likewise gives an insight to the possible ways of addressing the quality of pellets during development.